2013
DOI: 10.1159/000355487
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Decrease in Central Retinal Thickness Predicts Visual Acuity Response to Intravitreal Ranibizumab in Diabetic Macular Edema

Abstract: Purpose: To characterize factors that may be associated with optimal or suboptimal response to ranibizumab intravitreal injections in diabetic macular edema (DME). Methods: Fifty-nine eyes with DME treated with ranibizumab were included. All underwent best-corrected visual acuity (BCVA) assessment and optical coherence tomography (OCT) at baseline, 3 and 6 months. Central retinal thickness (CRT) was assessed at each visit, and OCT images were classified according to their morphological patterns. Results: A mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Although improvements in VA were not statistically significant at the 4- or 6-month visit, VA did improve as CST decreased among our patients. Santos et al [ 32 ] also reported correlations between decreased CST and improved VA. Long-standing DME that does not respond to treatment might lead to photoreceptor damage and visual impairment [ 33 ]. Therefore, preventing long-standing DME is important for avoiding severe visual loss.…”
Section: Discussionmentioning
confidence: 96%
“…Although improvements in VA were not statistically significant at the 4- or 6-month visit, VA did improve as CST decreased among our patients. Santos et al [ 32 ] also reported correlations between decreased CST and improved VA. Long-standing DME that does not respond to treatment might lead to photoreceptor damage and visual impairment [ 33 ]. Therefore, preventing long-standing DME is important for avoiding severe visual loss.…”
Section: Discussionmentioning
confidence: 96%
“…Spectral-domain OCT is a commonly used commercial objective method for measuring retinal thickness, particularly CMT [25]. CMT is significantly correlated with VA in preterm children [32] or pediatric patients with diagnosed retinal diseases [33].…”
Section: Discussionmentioning
confidence: 99%
“…We used spectral-domain OCT (iTVue SD-OCT; Optovue Inc. Fremont, CA, U.S.A.) to evaluate the bilateral central macular thickness (CMT) of the included children with unilateral congenital cataract at 3 months after surgery [24, 25]. The macula was divided into three concentric circles with radii of 1, 3 and 6 mm, separately.…”
Section: Methodsmentioning
confidence: 99%
“…They found that BCVA improved from 4.78 and 5.52 letters, and a central retinal thickness decreased from 80.25 and 106.12 microns after 3 and 6 months of treatment. They concluded that optimal responders to anti-VEGF therapy could be identified based on their response to decrease in central retinal thickness and hence, could be a predictor of BCVA improvement after the treatment 16 .…”
Section: Discussionmentioning
confidence: 99%